Assessment of satisfaction of undergraduate intern medics according to an educative model in the Hospital General de México - José Francisco González Martínez; Julio Herminio Pimienta Prieto; José de Jesús Rivera Sánchez; Juan Carlos Paredes Palma (Revista Médica del Hospital General de México, 2015)
Quality medical education can only be achieved if it is evaluated using a valid instrument. To evaluate user satisfaction, here, that of undergraduate interns, a multimodal ad hoc questionnaire was validated to rate professors, the program content, the didactic material and the facilities for three different generations of medics. The results showed consistency and reliability in 14 cases (α Cronbach of 0.863 with Bartlet test of X2 102.8, p = 0.001). By contrasting the changes before and after the internship, a statistically significant change could only be perceived in relation to the content (p = 0.04), material (p = 0.04) and facilities (p = 0.0001) in the 2011 generation. Generally speaking, the global ratings for the three different generations were good or excellent.